(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article discusses the peculiarities of the process of globalization in the world, the increasing desire of countries of the world to choose a truly democratic path that serves the interests of humanity, the increasing role of information in such a situation, and the fact that humanity is experiencing revolutionary changes in the field of information.